(untitled) (UCC Student Medical Journal, 2026)
The field of obstetrics and gynecology (OBGYN) is integral to women’s health, encompassing preventive care, pregnancy, and reproductive health. However, significant cultural, racial, and ethical challenges persist, impacting patient outcomes and equity. This narrative review highlights key issues in OBGYN care, including disparities driven by communication barriers, racial bias, and restricted access to reproductive services. The relationship between language discordance and obstetric trauma for non-English speakers, emphasizing the need for interpreter services and bilingual proficiency among providers. Racial bias manifests in higher maternal mortality rates for Black women and inadequate pain management due to unfounded beliefs about biological differences. Ethical challenges also arise, concerning access to abortion and prenatal screening services, with wide global variation in legislation and implementation. In Ireland, restrictive laws and a lack of universal non-invasive prenatal testing (NIPT) highlights barriers to informed decision-making. Future directives emphasize fostering diversity in healthcare teams, implementing educational programs to address stigma, and advocating for inclusive policies that ensure equitable care. By addressing these challenges, OBGYN care can evolve to reflect the principles of equity, representation, and inclusivity, ultimately improving outcomes for diverse patient populations.